2021
DOI: 10.23887/jiku.v8i3.30709
|View full text |Cite
|
Sign up to set email alerts
|

Identifikasi Permainan Dan Olahraga Tradisional Kabupaten Gorontalo

Abstract: Penelitian ini bertujuan untuk mengidentifikasi apa saja permainan dan juga olahraga tradisional yang ada di Kabupaten Gorontalo. Penelitian ini merupakan penelitian kualitatif dengan metode observasi, wawancara, dokumentasi, triangulasi atau gabungan yang menggunakan istrumen kuisioner dalam pengumpulan data. Objek dalam penelitian ini adalah beberapa tokoh budaya setempat yang ada di Kabupaten Gorontalo. Adapun temuan dari penelitian ini ada beberapa jenis permainan dan olahraga tradisional di Kabupaten Goro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 0 publications
0
8
0
4
Order By: Relevance
“…This first question is about knowledge about Langa. Langga itself is a traditional martial art in Gorontalo Province, Indonesia [9]. Of course, Langga is often played in the area.…”
Section: Do You Know About the Traditional Langga Martial Arts?mentioning
confidence: 99%
See 1 more Smart Citation
“…This first question is about knowledge about Langa. Langga itself is a traditional martial art in Gorontalo Province, Indonesia [9]. Of course, Langga is often played in the area.…”
Section: Do You Know About the Traditional Langga Martial Arts?mentioning
confidence: 99%
“…Previous research has been carried out by observers of traditional games and traditional sports in the province of Gorontalo, Indonesia, who concluded that the Langga martial art has become part of the culture in Gorontalo and its surroundings [9]. The importance of this research is because there is no research conducted in exploring the interest of the Langga Martial Arts for junior high school students who are expected to be the successors of the next generation of customers.…”
Section: Introductionmentioning
confidence: 99%
“…Perlahan tapi pasti, masuknya teknologi yang berasal dari luar negeri mulai mengikis permainan dan olahraga tradisional yang ada. Permainan yang dulunya menggunakan peralatan seadanya yang mudah dijumpai di sekitaran rumah mulai beralih ke teknologi yang berkembang (Hadjarati & Haryanto, 2020).…”
Section: Pendahuluanunclassified
“…Pada masa perkembangan ini mereka sangat dituntut untuk aktif bergerak demi untuk tumbuh kembang anak itu sendiri ke depannya. Salah satu permainan tradisonal asli Gorontalo (Hadjarati & Haryanto, 2020) Sosialisasi ini melibatkan mahasiswa dalam membantu pelaksanaan.…”
Section: Pendahuluanunclassified